Analysis of design and technological features of gear pumps - Zharkevich О.М.; Nikonova Т.Ю.; Gierz Л.; Berg А.С.; Berg А.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article presents the main design and technological features of gear pumps with a description of the contacts of the gear wheels during their interaction and manufacturing accuracy. The increase in contacts in the interdental space reduces the pulsation by 75%, the noise level by 5 decibels. The use of helical gears increases the efficiency of gear pumps and reduces pulsation. External gear pump with axial compensation with high precision and high quality materials resistant to fatigue. Internal gear pumps have a compact body and are less noisy. In practice, external gear pumps are most commonly used due to their simple design and low cost. The gear pump housing is subject to wear due to high pressure. During operation of the pump, uneven stresses occur, which leads to fatigue loads on the shaft in one direction. Additional pulsation entails oscillations of the structure. The gear pump’s own vibrations contribute to its failure, especially if the rotation speed is 100,000 cycles. During the operation of a gear pump, noise occurs that can be dampened with silencers or dampers, which increases the price of the pump. The interdental spaces of a gear pump are prone to cavitation during sudden pressure surges, which increases wear. To eliminate wear, pulsation, vibration, noise, a new design of the gear pump is proposed using various types of oils and methods for correcting the shape of the teeth.